Well-Posedness and Stability Result of the Nonlinear Thermodiffusion Full von Kármán Beam with Thermal Effect and Time-Varying Delay - Abdelbaki Choucha; Djamel Ouchenane; Salah Mahmoud Boulaaras; Bahri Belkacem Cherif; Mohamed Abdalla (Journal of Function Spaces)
In this work, we consider a new full von Kármán beam model with thermal and mass diffusion effects according to the Gurtin-Pinkin model combined with time-varying delay. Heat and mass exchange with the environment during thermodiffusion in the von Kármán beam. We establish the well-posedness and the exponential stability of the system by the energy method under suitable conditions.